IMPLEMENTASI KEBIJAKAN KOMUNITAS BELAJAR DALAM PENGEMBANGAN KEPROFESIAN BERKELANJUTAN (PKB) GURU SEKOLAH DASAR NEGERI LANGGENG KECAMATAN TLOGOMULYO KABUPATEN TEMANGGUNG - Anjar Wikaningrum; Ngurah Ayu Nyoman Murniati; I Made Sudana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Wikaningrum, Anjar. 2024. Implementation of Learning Community Policy in the Development of Sustainable Professionalism (PKB) for Teachers at Langgeng State Elementary School. Thesis. Study Program of Educational Management. Postgraduate Program of Universitas PGRI Temanggung. Advisors: 1) Dr. Ngurah Ayu Nyoman Murniati, M.Pd., Advisors 2) Dr. I Made Sudana, M.Pd. This study aims to describe the implementation of the learning community policy in the development of sustainable professionalism for teachers at Langgeng State Elementary School, Tlogomulyo District, Temanggung Regency. The method used in this research is qualitative with a descriptive approach. Data were collected through interviews, observations, and documentation. The results of the study indicate that effective communication between the principal and teachers plays a crucial role in the successful implementation of the learning community. Adequate human resources, support for facilities and infrastructure, and a positive attitude of teachers towards professional development are also determining factors in the success of this program. A supportive and flexible bureaucratic structure facilitates the implementation of the policy, allowing the learning community to operate smoothly and effectively. This research is expected to contribute to the development of education in Indonesia, particularly in enhancing the quality of teaching through learning communities.